KERJA SAMA TIM DAN SINERGI ORGANISASI: INTEGRASI PERSPEKTIF MANAJEMEN DAN HADIS - Alfisyah; Misda Ariyani; Fahmi Riady; Suraijiah; Rusdiana (PT. Hasba Edukasi Mandiri, 2026)
Teamwork and organizational synergy are important factors in building effective, harmonious, and sustainable Islamic educational organizations. The development of modern organizations shows that institutional success is determined not only by individual abilities but also by the capacity to build collective work, collaboration, and effective communication among organizational members. This article aims to examine the concept of teamwork and organizational synergy from an Islamic perspective based on the Hadith of Prophet Muhammad SAW and its relevance to the management of Islamic educational organizations. This study employed a library research method using a content analysis approach. Data were collected from Hadith, Qur’anic verses, organizational management books, scientific journals, and previous studies relevant to collective work and organizational synergy. The findings indicate that collective work in Islam emphasizes the values of coordination, communication, shared commitment, and interdependence among organizational members. The Hadith of the Prophet also highlights the importance of solidarity, mutual assistance (ta‘āwun), togetherness, and unity in building strong and harmonious organizations. Furthermore, synergy and collaboration contribute significantly to improving organizational effectiveness, strengthening working relationships, and creating an organizational culture based on ukhuwah (brotherhood) and togetherness. Therefore, teamwork and organizational synergy in the Islamic perspective are not only oriented toward achieving organizational goals but also contain spiritual dimensions and worship values.